2012
DOI: 10.1089/end.2011.0416
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopic Lithotripsy for Distal Ureteral Calculi: Comparative Evaluation of Three Different Lithotriptors

Abstract: The three lithotripsy devices evaluated behaved similarly in terms of the ability to fragment stones, and were equally effective for distal ureteral stones. Adequate fragmentation and fragment removal are mainly dependant on stone size and surgical technique (use of auxiliary wire).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…In this study we observe 100% success rate with laser lithotripter and 94.73% with pneumatic lithotripsy. Similarly, Salvado et al (18) also reported 96% success rate of laser lithotripsy in the management of distal ureteral stone. Manohar et al (19) reported 84% success rate with laser lithotripsy.…”
Section: Discussionmentioning
confidence: 85%
“…In this study we observe 100% success rate with laser lithotripter and 94.73% with pneumatic lithotripsy. Similarly, Salvado et al (18) also reported 96% success rate of laser lithotripsy in the management of distal ureteral stone. Manohar et al (19) reported 84% success rate with laser lithotripsy.…”
Section: Discussionmentioning
confidence: 85%
“…Kassem [9] indicated success rate of laser lithotripsy as 12.9%, in the management of ureteral stones longer than 12.9 mm. However, Salvado et al [10] expressed the success rate of laser lithotripsy in the management of distal ureteral stone as 96 percent. According to Cimino et al [36] overall success rate of laser lithotriptors in the management of all ureteral stones is 86.1 percent.…”
Section: Discussionmentioning
confidence: 99%
“…Razzaghi et al [4] detected incidence of stone migration into renal collecting system as 17.9% in the PL group but, without such a complication (0%) in the laser group. Salvado et al [10] compared PL, and LL groups as for stone migration without any difference between groups. Manohar et al [8] reported stone migration rates as 24, and 16% for LL, and PL groups, respectively, without any statistically significant difference between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerrahi işlemlerin belirli sınırlar içerisinde kabul edilebilir komplikasyon oranları mevcut olup, endoskopik bir yöntem olan URS'nin de kendine özgü komlikasyonlarının olabileceği ve hatta ölümle sonuçlanabileceği göz ardı edilmemelidir. (5)(6)(7)(8) .…”
unclassified